2022
DOI: 10.1177/17588359221119370
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of SARS-CoV-2 vaccines in patients with breast cancer

Abstract: Purpose: To explore the immunogenicity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in patients with breast cancer based on type of anticancer treatment. Methods: Patients with breast cancer had anti-spike antibody concentrations measured ⩾14 days after receiving a full SARS-CoV-2 vaccination series. The primary endpoint was IgA/G/M anti-spike antibody concentration. Multiple regression analysis was used to analyze log10-transformed antibody titer concentrations. Results: Between 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…We speculate that this surprising result could be due to the different types of mRNA vaccine used in cirrhotic patients (Moderna, 1273 mRNA vaccine) and in the HCWs reference group (Pfizer-BioNTech, BNT162b2 mRNA vaccine). Our hypothesis is supported by previously published studies where the Moderna-1273 mRNA vaccine induced significantly higher anti-S titers compared to other types of vaccination in the general population [28][29][30] and in immunocompromised subjects [31,32]. In addition, two studies evaluating the effectiveness of COVID-19 vaccination in cirrhotic patients demonstrated that a single dose of Johnson & Johnson vaccine [21] or two doses of BNT162b2 mRNA vaccine [24] were associated to a suboptimal antibody response.…”
Section: Discussionsupporting
confidence: 85%
“…We speculate that this surprising result could be due to the different types of mRNA vaccine used in cirrhotic patients (Moderna, 1273 mRNA vaccine) and in the HCWs reference group (Pfizer-BioNTech, BNT162b2 mRNA vaccine). Our hypothesis is supported by previously published studies where the Moderna-1273 mRNA vaccine induced significantly higher anti-S titers compared to other types of vaccination in the general population [28][29][30] and in immunocompromised subjects [31,32]. In addition, two studies evaluating the effectiveness of COVID-19 vaccination in cirrhotic patients demonstrated that a single dose of Johnson & Johnson vaccine [21] or two doses of BNT162b2 mRNA vaccine [24] were associated to a suboptimal antibody response.…”
Section: Discussionsupporting
confidence: 85%
“…Most studies evaluated the 2-dose primary series (n = 81, 82.7%). Patients received 2 doses of the primary series followed by 1 booster dose in 17 studies (17.3%) [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Most studies did not specify whether the mRNA-1273 booster dose was a true booster (i.e., 50 mcg mRNA/dose) or a third dose of the primary series (i.e., 100 mcg mRNA/dose).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…These changes would have a positive impact on vaccination outcomes because they trigger a "viral mimicry" response, characterized by interferon production and expression of interferon-stimulated genes (31,32). Nonetheless, several clinical trials have observed impaired humoral responses after an initial two-dose series for patients receiving CDK4/6 inhibitors (12)(13)(14). Regardless of the diversity of the control group in these studies (patients on endocrine therapy or healthy volunteers), the serological findings of the current research are widely consistent with the available evidence.…”
Section: A B Cmentioning
confidence: 99%
“…Currently, breast cancer patients receive different kinds of therapy, with monoclonal antibodies against human epidermal growth factor receptor 2 (HER2) and cyclindependent kinase 4/6 (CDK4/6) inhibitors being the most commonly used targeted agents (9,10). While limited data are available on HER-2-targeted therapies (11), the relationship between CKD4/6 inhibitors and the efficacy of vaccination remains controversial and concerns only the first or second immunization (12)(13)(14)(15)(16). Secondary neutropenia and lymphopenia occurring in most patients on CDK4/6 inhibition may hamper immune responses to vaccination (17).…”
Section: Introductionmentioning
confidence: 99%